Self-actualization and subjectivity in young men looking for a new job - N. A. Tsvetkova (Вестник университета, 2023)
The study subject is self-actualization and subjectivity in men looking for work. The purpose of this research is to identify the features of their self-actualization and subjectivity. Such methods of psychodiagnostics as the “SAT” technique by E. Shostrom (adapted by Yu.E. Aleshina et al.); the “URSL” test by M.A. Shchukina were used. Taking into account the main results of the study, the author came to the conclusion that the sample as a whole revealed problematic self-actualization and a fairly high overall level of subjectivity. In 83% of respondents, self-actualization was revealed only by contact. The proportion of men who recognize the values of a self-actualizing personality was 34%. A direct close connection between self-actualization and subjectivity has been established. The field of application of the found results is the social psychology of personality (the data received are important for assessing the socio-psychological readiness of men to promptly solve the problem of employment using intrapersonal resources). Mentioning the prospects of the study, it should be advisable to perform a comparative analysis of data by gender. The results obtained are valuable for practical social psychologists in terms of helping young men who find it difficult to realize their intentions to find a new job due to problematic self-actualization and insufficient subjectivity.